Hydrogen Energy Storage in China’s New-Type Power System: Application Value, Challenges, and Prospects - Xu Chuanbo; 2; Liu Jianguo (中国工程科学, 2022)
Accelerating the development of the hydrogen energy industry is crucial for realizing the carbon peaking and carbon neutralization goals and for ensuring national energy security. Hydrogen energy storage has the advantages of cross-seasonal, crossregional, and large-scale storage, as well as quick response capabilities, which is applicable to all links of “source/grid/load” of a newtype power system. This study analyzes the advantages of hydrogen energy storage over other energy storage technologies, expounds on the demands of the new-type power system for hydrogen energy, and constructs an application value system for hydrogen energy storage in the “source/grid/load” of the new-type power system. The results show that hydrogen energy storage can satisfy the requirements of the new-type power system in terms of storage capacity and discharge time; however, gaps remain in investment cost and conversion efficiency. The hydrogen energy system lacks coordination with the power system, and the application of hydrogen energy storage to the new-type power system lacks incentive policies. Moreover, standards systems are insufficient or even absent in renewable energy hydrogen production, electric–hydrogen coupling operation control, and hydrogen fuel cell power generation. Therefore, we suggest that the electric – hydrogen storage mode with high efficiency and low cost should be primarily used at present, and the electric – hydrogen–electric mode should be auxiliary. It is imperative to give full play to the power of hydrogen, electricity, and carbon markets to promote the low-carbon and low-cost development of hydrogen energy storage; actively explore the combination of hydrogen energy transport modes at different distance scales to solve the problem of mismatched distribution of hydrogen energy resources and loads; and accelerate the development of a new standards system for the electric–hydrogen coupling industry.